Barriers and enablers of 1.5° lifestyles: Shallow and deep structural factors shaping the potential for sustainable consumption - Hirth, Steffen; Kreinin, Halliki; Fuchs, Doris; Blossey, Nils; Mamut, Pia; Philipp, Jeremy; Radovan, Isabelle; , The EU1.5°Lifestyles Consortium; Antal, Orsolya; Belousa, Inga; Bösch, Martha; Brizga, Janis; et al. (Frontiers in Sustainability, 2023)
Introduction Transforming consumption and lifestyles toward sustainability cannot be achieved by individual behavior change alone but requires changes in the structures in which this behavior is embedded. However, “structure” is a blurry concept and scholars use it in a multitude of ways. What often remains implicit in studies on structural phenomena are different types of structures, how they may or may not restrict the agency of individuals in particular ways, and how these restrictions support sustainable consumption patterns at the societal level. To move beyond the current state of research, this article systematizes political, economic, technological, and societal structural factors the literature identifies as impactful regarding the sustainability of consumption and lifestyles compatible with the targets of the Paris Agreement. Methods We draw on a systematic review of existing research and use empirical observations to develop conceptual terms that revisit the structure-agency dilemma and offer ways going forward about (un)sustainable consumption. Results We do so based on the material or ideational, as well as shallow or deep nature of these factors. Thereby, the article throws light on the deep and opaque material and ideational structural factors lying underneath and shaping the sustainability impact of the more visible, shallow structural factors typically considered in public debates about sustainability governance. Discussion The article, thus, highlights the need to consider and address these deep structural factors for any effective pursuit of transformation.